Tracking a Circular Economy Transition Through Jobs: Method Development and Application in Two Cities - Muñoz H., M. Esteban; Novak, Marijana; Gil, Sharon; Dufourmont, Joke; Goodwin Brown, Esther; Confiado, André; Nelemans, Mathijs (Frontiers in Sustainable Cities, 2022)
The methodology presented in this paper produces a circular economy jobs (CE jobs) measure. Using jobs as a proxy indicator, these measure gives cities a robust number to indicate progress towards the circular economy and is designed to serve as a first step in developing a circular economy strategy. The CE jobs measure tracks the inputs and outputs of goods in a city’s ‘’boundaries’’ through the material import dependency of the city’s economic sectors. At the same time, tracking and assessing the circularity of the local jobs in these economic sectors will also provide city leaders with an indication of which sectors circularity is happening and could potentially happen. This paper also concludes that the process of coming to the CE jobs has two parts, the first more relevant to the local government and the second better influenced by the national government. Both need to come together for a truly circular local economy to happen.